Multi-Sensory-Based Qur’an Reading Training for Students of Pesantren Hasanuddin, Gowa Regency - Muhammadong Muhammadong; Khaerunnisa Khaerunnisa; Sitti Muthmainnah; Nurhilaliyah Nurhilaliyah (Lumbung Pare Cendekia, 2026)
For students (santri), being able to read the Qur'an is a basic part of their religious education. The first observations at Pesantren Hasanuddin in Gowa Regency showed that a lot of pupils, especially new ones, had trouble reading letters, saying tajwid rules, and understanding recitation. Given this situation, a multi-sensory Qur'an reading training method was chosen to enhance learning efficacy through visual, aural, and kinesthetic modalities. The approach employed was a pre-experimental design using a one-group pretest-posttest framework. Thirty children took part in the four-week instruction, which included seeing Arabic letters, listening to correct recitations, and writing and saying letters to practice their kinesthetic skills. Before and after the instruction, the pesantren instructors used exams that had been validated to measure how well the students could read the Qur'an. The results showed that the average score on the pretest went up from 60.7 to 85.3 on the posttest, which means that the ability to read the Qur'an got a lot better. This shows that the multi-sensory method works to improve letter recognition, tajwid mastery, and students' confidence. In conclusion, the multi-sensory Qur'an reading training has been shown to greatly help kids read better. Thus, it is advisable to adopt this as a learning model for other Islamic boarding schools to improve Qur’anic literacy.